2019
DOI: 10.1016/j.heliyon.2019.e02946
|View full text |Cite
|
Sign up to set email alerts
|

Cocrystal construction between the ethyl ester with parent drug of diclofenac: structural, stability, and anti-inflammatory study

Abstract: This study aimed to collect the crystallographic data of ethyl diclofenac and discover a cocrystal from this ester with its parent, diclofenac acid, and to investigate their physicochemical properties and anti-inflammation activity. Firstly, ethyl diclofenac single crystal was isolated and continued by the cocrystal screening and isolation. Solid characterization was conducted by thermal analysis, infrared spectroscopy, powder x-ray diffractometry, followed by structural determination using a single crystal x-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Based on dissolution profiles on pH 1.2 medium ( Figure 17 a), the maximum drug release from all samples (ND, NDPM, and NDPT) was achieved after 15 min dissolution, but in a very low concentration. This result was in line with the information from references [ 26 , 49 , 58 ]. Due to the acidity of ND (pKa: 4, at 25 °C), it showed that in the gastric medium, each sample was not completely separated because hydrogen ions inhibited diclofenac dissociation.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Based on dissolution profiles on pH 1.2 medium ( Figure 17 a), the maximum drug release from all samples (ND, NDPM, and NDPT) was achieved after 15 min dissolution, but in a very low concentration. This result was in line with the information from references [ 26 , 49 , 58 ]. Due to the acidity of ND (pKa: 4, at 25 °C), it showed that in the gastric medium, each sample was not completely separated because hydrogen ions inhibited diclofenac dissociation.…”
Section: Resultssupporting
confidence: 92%
“…However, NDPM was superior in increasing the percentage of drug release. Based on the Henderson–Hasselbach’s equation at a pH below the pKa of ND, the percentage of non-ionized substance will be greater than at a pH above the pKa so that the percentage of substances absorbed into the solute tends to increase [ 55 , 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…APPENDIX A References to experimental data used in this work Sorted alphabetically by CSD refcodes: ACUCIN (Nikonova et al, 2018), ADOWUO (Hermann et al, 2017), AHUKIZ (Weber et al, 2015), AMEPOS (Janicki & Starynowicz, 2010), ARAQUH (Hemgesberg et al, 2016), BECFAT (Veronelli et al, 2017), CAMVES (Dittrich et al, 2002), DAYCEO (Uppal et al, 2017), DNEDAM01 (Gruhne et al, 2021), DUBWAB (Nugrahani et al, 2019), DUCMAQ (Grabowsky et al, 2009), EDAWIP (Evans & Gilardi, 2001), EGUFIY (Malassis et al, 2019), GLYALB08 (Capelli et al, 2014), IYAQOP02 (Marshall et al, 2016), KOVPIX (Thanzeel et al, 2019), LETHIE (Chen et al, 2018), LOKPOT (Ballmann et al, 2019), LOSLEL (Johnas et al, 2009), MANMUJ08 (Jorgensen et al, 2014), MOSCOP (Clegg, 2019), MOVPIZ (Lapointe et al, 2019), MUHBOI (Butschke et al, 2015), OXACDH46 (Kamin ´ski et al, 2014), PCYPOL04 (Mohanraj et al, 2018), PPHCHN11…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the ED and DFA co-crystal were chemically stable. Moreover, anti-inflammatory activity was studied using five groups of mice, which showed that the co-crystals between ED and DFA increased anti-inflammatory activity more than the single components [ 50 ].…”
Section: Progress On Nsaid Co-crystalsmentioning
confidence: 99%